Happy to be nappy - Hooks, Bell; Chris raschka (New york : Hachette book group, 2017)
Celebrates the joy and beauty of nappy hair.
Happy to be nappy, Happy with hair all short and strong, Just all girl happy.
Keywords: African Americans; African Americans Health and hygiene Fiction; African Americans Juvenile fiction; Board books